STATUS HUKUM IBU TIDAK MENYUSUI BAYI DAN SOLUSI PENCEGAHANNYA - Agus Nurcholis Saleh (JURIS (Jurnal Ilmiah Syariah), 2018)
Much research has been done on breast milk. The results are significant. But the rate of early breastfeeding and exclusive breastfeeding is still far from expectations. Moreover, modernization and globalization have succeeded in encouraging women to work. The term, career woman. Unfortunately, the woman forgot her nature as the only supplier of ASI. Be, many babies whose rights are not fulfilled. This study relates the ASI signiﬁcance, including the legal status for women who leave ASI. This study method is literature. The author collects literature on ASI, and legal consequences for those who "intentionally" leave their breastfeeding obligations. The author reads the Qur'an as the main source of analysis. The previous research report became the validation of the main source. This study is written descriptively with the deductive method. This research produced three things. First, they are treacherous towards the mandate of Allah SWT. Second, there are three inherent statuses for mothers who refuse to breastfeed: betrayal, destruction, and debt. Third, the husband must guide his wife to prepare herself as best as possible in the face of pregnancy, birth, and breastfeeding, so that the duties and mandates are realized.